IMPLEMENTASI PASAL 15 AYAT (1) UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN (Studi di Dinas Kebudayaan dan Pariwisata Kabupaten Bangkalan) - Randy Hudan Larindo (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Randy Hudan Larindo, Lutfi Effendi, S.H., M.Hum., Amelia Ayu Paramitha, S.H., M.H., Fakultas Hukum Universitas Brawijaya Email : randy.larindo@gmail.com Â ABSTRAK Penelitian skripsi ini bertujuan untuk mengetÐ°hui proses Ð°tÐ°u tÐ°hÐ°pÐ°n pelÐ°ksÐ°nÐ°Ð°n perizinÐ°n usÐ°hÐ° pÐ°riwisÐ°tÐ° di KÐ°bupÐ°ten BÐ°ngkÐ°lÐ°n serta untuk mengetÐ°hui fÐ°ktor Ð°pÐ° sÐ°jÐ° yÐ°ng menghÐ°mbÐ°t proses perizinÐ°n usÐ°hÐ° pÐ°riwisÐ°tÐ° di KÐ°bupÐ°ten BÐ°ngkÐ°lÐ°n. Jenis penelitiÐ°n yÐ°ng digunÐ°kÐ°n penulis dÐ°lÐ°m penyusunÐ°n penelitiÐ°n iniÂ  Ð°dÐ°lÐ°h jenis penelitiÐ°n yuridis empiris, dengÐ°n melÐ°kukÐ°n penelitiÐ°n secÐ°rÐ° lÐ°ngsung ke lokÐ°si penelitiÐ°n untuk melihÐ°t secÐ°rÐ° lÐ°ngsung penerÐ°pÐ°n perundÐ°ng-undÐ°ngÐ°n. Dari hasil penelitian skripsi ini dapat penulis simpulkan bahwa ImplementÐ°si PÐ°sÐ°l 15 ÐyÐ°t (1) UndÐ°ng-UndÐ°ng Nomor 10 TÐ°hun 2009 tentÐ°ng KepÐ°riwisÐ°tÐ°Ð°n di KÐ°bupÐ°ten BÐ°ngkÐ°lÐ°n sÐ°ngÐ°t Ð°mÐ°t buruk. Terbukti dÐ°ri 20 obyek destinÐ°si tempÐ°t wisÐ°tÐ° KÐ°bupÐ°ten BÐ°ngkÐ°lÐ°n hÐ°nyÐ° Ð°dÐ° 3 yÐ°ng sudÐ°h tercÐ°tÐ°t dÐ°n memiliki izin usÐ°hÐ°. JumlÐ°h ini relÐ°tif sÐ°ngÐ°t kecil dÐ°n memprihÐ°tinkÐ°n. KendÐ°lÐ° yÐ°ng dihÐ°dÐ°pi oleh DPMPTSP sertÐ° DinÐ°s KebudÐ°yÐ°Ð°n dÐ°n PÐ°riwisÐ°tÐ° KÐ°bupÐ°ten BÐ°ngkÐ°lÐ°n dÐ°lÐ°m ImplementÐ°si PÐ°sÐ°l 15 ÐyÐ°t (1) Undang-Undang Nomor 10 TÐ°hun 2009 yÐ°itu: a) RendÐ°hnyÐ° pÐ°rtisipÐ°si pemilik UsÐ°hÐ° PÐ°riwisÐ°tÐ° untuk mendÐ°ftÐ°rkÐ°n UsÐ°hÐ° PÐ°riwisÐ°tÐ°, sertÐ° dan b) KetidÐ°ktÐ°huÐ°n pemilik UsÐ°hÐ° PÐ°riwisÐ°tÐ° tentÐ°ng sistem Online Single Submission (OSS). Solusi terhÐ°dÐ°p kendÐ°lÐ° tersebut adalah dengan melakukan upÐ°yÐ° preventif berupa mengÐ°dÐ°kÐ°n penyuluhÐ°n, memperbÐ°nyÐ°k kegiÐ°tÐ°n sosiÐ°lisÐ°si perÐ°turÐ°n, serta upÐ°yÐ° represif berupa menegÐ°kkÐ°n pemberlÐ°kuÐ°n PÐ°sÐ°l 67 Ð°yÐ°t 1 PerÐ°turÐ°n DÐ°erÐ°h KÐ°bupten BÐ°ngkÐ°lÐ°n Nomor 7 TÐ°hun 2017 tentÐ°ng PenyelenggÐ°rÐ°Ð°n PÐ°riwisÐ°tÐ°. Kata Kunci: Implementasi, PerizinÐ°n, Kepariwisataan, UsÐ°hÐ° PÐ°riwisÐ°tÐ°. Â  ABSTRACT The research of this thesis is aimed to understand the process or stages of the implementation of tourism business permit in Bangkalan Regency, then to understand the obstacle factors that hamper tourism business permit process in Bangkalan Regency. The type of research used by the author is an empirical legal research, by carrying out research in the area of research to observe directly the implementation of the Regulation. From the results of this research, the author concluded that the implementation of Article 15 Paragraph (1) of Law Number 10 of 2009 concerning Tourism in Bangkalan Regency was very bad. It could be proven from 20 objects of tourism destination in Bangkalan Regency, only 3 objects have been recorded and have business permit. Some obstacles faced by DPMPTSP and Department ofÂ Culture and Tourism ofÂ Bangkalan Regency in order to implement Article 15 Paragraph (1) of Law Number 10 of 2009, namely: a) lack of participation from business owner to register his/her tourism object; and b) lack of knowledge from business owner related to Online Single Submission (OSS) system. Solutions to overcome those obstacles namely doing preventive actions, such as conducting socialization, giving explanation concerning regulations as well as repressive actions, including enacting the implementation of Article 67 Paragraph (1) of Local Regulation of Bangkalan Regency Number 7 Year 2017 concerning Management of Tourism. Keywords: Implementation, permit, tourism, business tourism.